Body Movement on Screen for Navigating Grief and Expressions of Care in The Seen & Unseen - Sekar Sari (Department of Anthropology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This article examines how The Seen & Unseen (Sekala Niskala, 2017), directed by Kamila Andini, deploys cinematic craft to shape body movement as a language for navigating grief and expressing care, especially in the contexts where care—typically enacted through direct physical encounter—must be articulated through screen-mediated bodily movement. Departing from Western, dialogue-centred film conventions, the film foregrounds gesture, choreography, stillness, and rhythm to articulate affective experience. Drawing on care ethics and Balinese cosmology, the study argues that the film reframes care as a sensorial and relational practice rather than a verbal or narrative one. Through close analysis of key sequences—including Tantri’s moon dance, the river immersion, and the rooster duel—the article explores how embodied movement functions as both a mourning ritual and an aesthetic offering of solidarity. It further situates the film within traditions of dance film, slow cinema, and indigenous performance, demonstrating how screen-mediated taksu, a culturally specific Balinese philosophy of embodied performance, enables affective transmission across distance through screen-based aesthetic mediation. By centering a child’s perspective through deliberate cinematic framing and rhythm, alongside Balinese performance epistemologies, The Seen & Unseen counters Hollywood’s dominance and reclaims cinematic authorship as a collaborative, intercultural, and embodied practice. Ultimately, the article proposes that movement-based cinema can create a shared field of sensorial attunement in which grief is collectively felt, and care is aesthetically enacted.